PERANAN WALI KELAS DALAM MENINGKATKAN KEDESIPLINAN PESERTA DIDIK SAAT PROSES PEMBELAJARAN DI SD NEGERI CENTRE MANGALLI GOWA - Nur Fadilah; Muhammad Rusmin B; Idah Suaidah; Akramunnisa; Awaliyah Musgamy (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The students who have not complied with school rules include those who do not arrive on time, some who do not wear school uniforms according to regulations, and others who do not follow classroom rules during lessons. Examples include students who do not pay attention when the teacher explains in front of the class, students who frequently leave and enter the classroom, and students who often bully their peers To identify and describe the role of the homeroom teacher in fostering student discipline during the teaching–learning process. To identify and describe the strategies used by the homeroom teacher to improve student discipline during the teaching–learning process. To identify and describe the obstacles faced by the homeroom teacher in increasing student discipline during the teaching–learning process. This research is descriptive qualitative research using a phenomenological approach at SD Negeri Centre Mangalli. Data collection methods used were observation, interviews, and documentation. The research instruments consisted of observation guides, interview guides, and documentation guides, with data analysis covering data reduction, data presentation, and drawing conclusions or verification. The validity of the data was checked using data triangulation techniques. The results of the study indicate that: 1) success in fostering student discipline is greatly influenced by the optimization of the homeroom teacher’s role in the teaching–learning process. 2) Integrated and continuous strategies produce optimal results in forming students’ disciplined character. 3) The obstacles faced by homeroom teachers in improving student discipline at SD Negeri Centre Mangalli Gowa are varied and complex. These obstacles stem from internal factors within the students as well as external factors such as family and environment.